English Speaking Club as a Means to Enhance Students' Communication Skills - Tonenchuk, Tetiana; Danylovych, Oksana; Mudra, Olena (My University, 2024)
This study investigates the effectiveness of an English Speaking Club as an extracurricular initiative at Yurii Fedkovych Chernivtsi National University. The purpose of the research is to describe main principles of planning the Speaking Club and analyse how it can boost motivation, enhance communication skills and confidence, and improve language command of the participants. The study employs a descriptive analytic method and student surveys to assess changes in speaking fluency, vocabulary, and overall interaction within the club. Main principles include a focus on student-centered learning, engagement in various interactive activities, and fostering of soft skills such as teamwork and critical thinking. The constituents of the planning process for the Club involve identifying the target audience, meeting frequency, communication channel, and the selection of topics. Event planning requires setting clear goals and expected outcomes for each meeting, designing activities to meet participants' needs and focus on particular skills development. The teacher’s role is stated as of a facilitator and moderator, providing a supportive learning environment and encouraging student initiative without direct evaluation. Self-evaluation and feedback are to be used to identify strengths and weaknesses, and to monitor progress over time. Results indicate significant improvements in students’ fluency, vocabulary expansion, alongside enhanced confidence and satisfaction with their learning experiences. The participants appreciated the informal and engaging setting, meaningful discussions and a collaborative environment. The findings underscore the importance of integrating extracurricular opportunities into language education, and dual benefits of improving linguistic capabilities and fostering essential life skills.
Keywords: ESP; Speaking Club; English language; communication; extracurricular